Psychometric Properties of the Bangla Version of the Beck Depression Inventory‐II (BDI‐II) With University Students in Bangladesh: A Cross‐Sectional Study - Md. Torun Hasan; Mozibul H. A. Khan (Health Science Reports)
ABSTRACT Background and Aims In clinical practice and research, the Beck Depression Inventory‐II (BDI‐II) is one of the most frequently employed and consistent depression assessment instruments. Despite numerous international studies thoroughly establishing the psychometric properties of the BDI‐II, no notable study has validated the scale in Bangladesh, especially on the student sample as well as in nonclinical settings. Therefore, the current study was conducted with a view to assessing the psychometric properties of the Bangla version of the BDI‐II in a sample of undergraduate students in the cultural context of Bangladesh. Methods The sample consisted of 1128 undergraduate students (55.9% males) aged from 18 to 28 (M = 22.35, SD = 1.41) from the university of Rajshahi, Bangladesh. The factor structure of the BDI‐II was investigated through confirmatory factor analysis (CFA). Results The CFA revealed that the hypothesized two‐factor model of the BDI‐II had an acceptable fit [χ2/df = 3.030, GFI = 0.957, TLI = 0.949, and CFI = 0.955, RMSEA = 0.042] in the current sample, which confirms the factorial validity of the Bangla version of the BDI‐II. Cronbach's α value (for total scale α = 0.90; for the cognitive‐affective factor α = 0.88; and for the somatic factor α = 0.73) assured high internal consistency. The concurrent validity of the BDI‐II was confirmed by the correlation with the Emotional Intelligence Scale (EIS) and the Brunel Mood Scale (BRUMS) in the expected direction. Conclusion The findings of the study suggest that the Bangla version of the BDI‐II is a valid instrument for assessing depression among the student community in Bangladesh. This study will also be very beneficial to research on mental health problems in Bangladesh.